Mathematical Model in Studying the Stability of Dynamic Systems - Le Hong, Lan (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2, 2017)
In this paper, the author investigated the phenomenon of flutter, which may be the cause of instability of construction structure when it is affected by aerodynamics. By analyzing the effect of aerodynamic on the structure via mathematical analysis, the author has established a mathematical model to study the stability of the structure in the aerodynamic flux that moves supersonically.